Synthesis of α,β′- and β,β′-Linked Dimethoxycarbonyldipyrromethanes by Rothemund-Type Condensation - Journot, Guillaume; Stoeckli-Evans, Helen; Neier, Reinhard (Synlett, 2012)
The Rothemund-type condensation of methoxycarbonylpyrrole with acetone produces mainly the α,β′-linked dipyrromethane, a building block for the synthesis of N-confused macrocycles. The influence of the reaction conditions on the regioselectivity of the process is reported. The X-ray structures of the α,α′-, α,β′- and β,β′-linked dipyrromethanes show an interesting discrimination of the structurally different types of hydrogen bonds.
Keywords: heterocycles; condensation; regioselectivity; pyrroles; hydrogen bonds